Democratization, governance, and poverty alleviation in the Autonomous Region in Muslim Mindanao. - Tanggol, Sukarno D. (Philippine Journal of Public Administration)
The creation of the Autonomous Region in Muslim Mindanao (ARMM) in 1989 along with the eventual laying down of arms of Moro National Liberation Front (MNLF) in 1996 suggested that a peaceful and developed Mindanao was in the offing. However, the rebellion of former MNLF head, turned-ARMM Governor Nur Misuari against the Philippine government, and the continuous armed struggle of the Moro Islamic Liberation Front illustrate the discontent with the governance of the Autonomous Regions. This study evaluates the 15 years of ARMM by going through the ideals of democratization, governance and poverty alleviation in the regions, and judging its success or failure.